FEATURES OF STATE REGULATION IN THE FIELD OF TOURISM IN FOREIGN COUNTRIES (Academia Science Repository, 2023)
The article discusses the main methods of state regulation of tourism, special national programs, direct subsidized financing of the industry, activities that stimulate inbound tourism. The features of the introduction of foreign experience in the state management of tourism in the Republic of Uzbekistan are substantiated.